2020
DOI: 10.1136/bmjopen-2020-037532
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations and associated factors of modern contraceptive use in Ethiopia: a spatial and multilevel analysis

Abstract: ObjectiveTo assess spatial variations in modern contraceptive use and to identify factors associated with it among married women in Ethiopia.DesignCross-sectional analysis of population-based and health facility data.SettingEthiopia Demographic and Health Survey data linked to Service Provision Assessment data.Population8473 married women and 1020 facilities that reported providing family planning services.MethodsA linked secondary data analysis of population and health facility data was carried out. Both mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(81 citation statements)
references
References 23 publications
(55 reference statements)
21
60
0
Order By: Relevance
“…Place of residence (urban, rural) and region (seven administrative divisions, namely Barishal, Chattogram, Dhaka, Khulna, Mymensingh, Rajshahi, Rangpur, Sylhet) were the communitylevel factors. To our knowledge, this is the first study in Bangladesh and other LMICs that considered the health facility-level factors because of their potential role in modern contraception use in SBI (21,27,28). We generated four health service variables: average distance to the nearest family planning facility, family planning service availability, readiness to provide family planning services, and general health facility readiness.…”
Section: Exposure Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Place of residence (urban, rural) and region (seven administrative divisions, namely Barishal, Chattogram, Dhaka, Khulna, Mymensingh, Rajshahi, Rangpur, Sylhet) were the communitylevel factors. To our knowledge, this is the first study in Bangladesh and other LMICs that considered the health facility-level factors because of their potential role in modern contraception use in SBI (21,27,28). We generated four health service variables: average distance to the nearest family planning facility, family planning service availability, readiness to provide family planning services, and general health facility readiness.…”
Section: Exposure Variablesmentioning
confidence: 99%
“…We generated four health service variables: average distance to the nearest family planning facility, family planning service availability, readiness to provide family planning services, and general health facility readiness. The details of this approach can be found elsewhere (28,29).…”
Section: Exposure Variablesmentioning
confidence: 99%
“…There was a variation among regions and city administrations regarding contraceptive use. A piece of information from EDHS 2016 showed that the variation observed was region-based (10). However, studies showed a continuous assessment of contraceptive use and their drawbacks, risks, and increasing societal commitment regarding the expansion of them to reduce the risk of unwanted pregnancy is necessary (11).…”
mentioning
confidence: 99%
“…And the status of the achievement of this policy with spatially informing studies is very crucial. Some studies applied multilevel analysis to identify related implementations when considering different clusters (10,23,24). Despite this, most studies in the country were dealing with contraceptive prevalence, side effects, and socio-demographic factors; regarding the distribution of intention at the country level through spatial mapping as there was little information in this area.…”
mentioning
confidence: 99%
“…Increased availability of the geographically referenced health facility and population data creates a window of opportunity to determine the precise effects of health facility-level and population-level factors on LAMC use. However, only a few studies conducted in LMICs [20][21][22][23] have examined these aspects in relation to contraception use in general and LAMC use in particular. Moreover, those studies did not present a stratified analysis of the influence of health facility-level factors on contraception use in rural and urban areas, despite substantial variations in the distribution of health facilities and contraception using patterns in rural and urban areas.…”
Section: Introductionmentioning
confidence: 99%